Global quantum differential operators on quantum flag manifolds, theorems of Duflo and Kostant - Backelin, E; Kremnizer, K (2011)
We give a short new proof for the theorem that global sections of the sheaf of quantum differential operators on a quantum flag manifold are given by the quantum group. As corollaries we retrieve Joseph and Letzter's quantum versions of classical enveloping algebra theorems of Duflo and Kostant. We also describe the center of the ad-integrable part of the quantum group and the adjoint Lie algebra action on it.